Ex Libris Dr A. C. M. Beukers / [Georg Rueter]. - Rueter, Pam Georg (1906-1998) ([wydawca nieznany], 1928)
W kwadrat wpisane koło, półpostać mężczyzny z laską Eskulapa w ręce, wokoło napis: Ex Libris Dr A. C. M. Beukers.